VETERINARY CAPACITY BUILDING AND FOOD SECURITY CHALLENGES IN DEVELOPING COUNTRIES - Johnson, Eugene (My University, 2017)
Veterinary capacity building is the transfer of technical knowledge and skills to individuals in an effort to create sustainable change, and for this report, it will focus on veterinary capacity building for the improvement of livestock production practices and food security in regions with limited resources, such as Guyana. In support of this goal, the veterinary engagements between the Guyana Livestock Development Authority (GLDA) and Farmer to Farmer (F2F) veterinary volunteers from 31 October to 18 November 2016 covered an extensive range of topics and training opportunities for veterinary professionals and staff of the GLDA. The team recognized several challenges for the veterinary community in Guyana and provided several recommendations for improvement in animal health services in a resource-limited situation. The F2F veterinary team thought that future engagements should target two levels of engagement based upon the expertise of prospective volunteers. One level of engagement should focus on training and skill development for veterinary professionals and livestock producers. The second level of engagement should involve assistance in the development of a strategic, time-structured plan for the implementation of an Active Animal Health Surveillance Program. Typically, the slaughter of meat animals in low-resource countries occurs in abattoirs or local butcher shops. Therefore, veterinary capacity building that focuses on improving sanitation levels surrounding the slaughter process would reduce foodborne public health risks to consumers. An adaptive approach that considers the local culture, social setting, and economic environment, will be paramount for successful opportunities with sustainable improvements in meat hygiene.
Keywords: Capacity Building; Meat Inspection; Guyana; Farmer-to-farmer; Slaughter; Food Security